A Proppian reading of the poetics of narration in mysterious poems of Hosn and Del and Jamal and Jalal - Isa Darabpour; Ali Garavand; Hassan Soltani kohbanani (مطالعات زبانی و بلاغی)
One of the approaches to structural analysis of narration is Vladimir Propp's morphology which focuses on characters actions. This descriptive and analytical research draws on Propp's morphology to analyze and compare  the narrative structure of verse romances Hosn and Del, by Molana Mohammad Ibn Yahya Sibak Neishabouri, with Jamal and Jalal byMohammad Nazl Abadi.’. Both these works, which have a mysterious and mystical substructure, are dealt with in this study to examine and evaluate their rate of efficiency and structural compatibility to Propp's model. The results of this comparative study indicate that these verse romances are similar in terms of structure, functions, and characters, and to a great extent compatible with Propp’s theory. The difference is that actions are   non-consecutive and there are omissions and additions of some functions in both narrations. Also, among Propp’s seven character types, some of characters are merged or removed due to similarities in their functions, depending on the storyline.